The scandal of reason : a critical theory of political judgment - Azmanova, Albena (New directions in critical theory., 2012)
Theories of justice struggle to balance vision and practicality. As with Habermas, the more demanding the ideal of justice, the less connected the theory is to political reality; as with Rawls, the more politically realistic the theory, the weaker its normative criteria, rendering the theory unreliable. Brokering a resolution to the?judgment paradox," Albena Azmanova advances a?critical consensus" model of judgment, which serves the normative ideals of a just society without resorting to ideal theory. Tracing the evolution of two major traditions in political philosophy?critical.